Hippocampal Transcriptomic Profiles: Subfield Vulnerability to Age and Cognitive Impairment - Ianov, Lara; De Both, Matt; Chawla, Monica K.; Rani, Asha; Kennedy, Andrew J.; Piras, Ignazio; Day, Jeremy J.; Siniard, Ashley; Kumar, Ashok; Sweatt, J. David; Barnes, Carol A.; Huentelman, Matthew J.; et al. (Frontiers in Aging Neuroscience, 2017)
The current study employed next-generation RNA sequencing to examine gene expression differences related to brain aging, cognitive decline, and hippocampal subfields. Young and aged rats were trained on a spatial episodic memory task. Hippocampal regions CA1, CA3, and the dentate gyrus were isolated. Poly-A mRNA was examined using two different sequencing platforms, Illumina, and Ion Proton. The Illumina platform was used to generate seed lists of genes that were statistically differentially expressed across regions, ages, or in association with cognitive function. The gene lists were then retested using the data from the Ion Proton platform. The results indicate hippocampal subfield differences in gene expression and point to regional differences in vulnerability to aging. Aging was associated with increased expression of immune response-related genes, particularly in the dentate gyrus. For the memory task, impaired performance of aged animals was linked to the regulation of Ca2+ and synaptic function in region CA1. Finally, we provide a transcriptomic characterization of the three subfields regardless of age or cognitive status, highlighting and confirming a correspondence between cytoarchitectural boundaries and molecular profiling.